Dermatology Residency Selection Criteria with an Emphasis on Program Characteristics: A National Program Director Survey - Farzam Gorouhi; Ali Alikhan; Arash Rezaei; Nasim Fazel (Dermatology Research and Practice)
Background. Dermatology residency programs are relatively diverse in their resident selection process. The authors investigated the importance of 25 dermatology residency selection criteria focusing on differences in program directors’ (PDs’) perception based on specific program demographics. Methods. This cross-sectional nationwide observational survey utilized a 41-item questionnaire that was developed by literature search, brainstorming sessions, and online expert reviews. The data were analyzed utilizing the reliability test, two-step clustering, and K-means methods as well as other methods. The main purpose of this study was to investigate the differences in PDs’ perception regarding the importance of the selection criteria based on program demographics. Results. Ninety-five out of 114 PDs (83.3%) responded to the survey. The top five criteria for dermatology residency selection were interview, letters of recommendation, United States Medical Licensing Examination Step I scores, medical school transcripts, and clinical rotations. The following criteria were preferentially ranked based on different program characteristics: “advanced degrees,” “interest in academics,” “reputation of undergraduate and medical school,” “prior unsuccessful attempts to match,” and “number of publications.” Conclusions. Our survey provides up-to-date factual data on dermatology PDs’ perception in this regard. Dermatology residency programs may find the reported data useful in further optimizing their residency selection process.